Race and College Admissions: An Alternative to Affirmative Action? - Long, Mark C. (The Review of Economics and Statistics, 2004)
During the late 1990s, several states eliminated affirmative action admissions policies at their public colleges. Some of these states substituted a program that grants admission to the top x% of each high school's graduating class. These new programs were instituted in efforts to restore minority college enrollments to their prior levels. This paper finds that the preferences given to minority applicants under affirmative action are large and that the minority share of admitted students in top-tier institutions would fall substantially after eliminating these preferences. However, there are not sufficient numbers of minorities in the top x% of their high school for the expected recovery from an x% program to be very large. Furthermore, most minority beneficiaries would have been accepted without these programs. As a result, x% programs are unable to replace traditional affirmative action and maintain the share of minority students.